Some kind of hate eaudiobook - Littman, Sarah Darer (Blackstone Publishing, 2022)
Declan Taylor is furious at the world. After winning state as a freshman starting pitcher, he accidentally messes up his throwing arm. Despite painful surgery and brutal physical therapy, he might never pitch again. And instead of spending the summer with his friends, Declan is forced to get a job to help his family out. On top of that, it seems like his best friend, Jake Lehrer, is flirting with Declan's crush and always ditching him to hang out with the team or his friends from synagogue. So Declan ends up playing a lot of Imperialist Empires online and making new friends. It's there he realizes he's been playing with Finn, a kid from his class. Finn is the first person who might be just as angry as Declan. As the two spend more time together, Finn also introduces Declan to others who understand what it's like when the world is working against you, no matter how much you try. How white kids like them are being denied opportunities because others are manipulating the system. And the more time Declan spends with Finn, the more he sees what they're saying as true. So when his new friends decide it's time to fight back, Declan is right there with them. Even if it means going after Jake and his family. And each new battle for the cause makes Declan feel in control of his rage, channeling it into saving his future. But when things turn deadly, Declan is going to have to decide just how far he'll go and what he's willing to sacrifice. In a stunning story set against the rise of white nationalism comes an unflinching exploration of the destruction of hate, the power of fear, and the hope of redemption.